(untitled) (Konferensiyalar | Conferences, 2024)
The given article is about imagery comparisons in the works of Engl ish writers. C omparison in the text of fiction performs various stylistic functions, the main of which are: the function of creating imagery, the function of emotional and intellectual assessment, expressive and super organizing functions. These comparison functions are associated with stylistic information transmitted through the stylistic device of comparison.